2000
DOI: 10.1089/10507250050137789
|View full text |Cite
|
Sign up to set email alerts
|

Review of Thyroid Cancer Cases Among Patients with Previous Benign Thyroid Disorders

Abstract: A previous register linkage study showed an increased risk of thyroid cancer among patients previously discharged from a hospital with a diagnosis of a benign thyroid disorder. In this study, we have reviewed all available medical records, first to validate the earlier result and second to describe the symptomatology of patients with a history of benign thyroid disorder prior to the cancer diagnosis. The previous study identified 189 patients with a benign and subsequent malignant thyroid disorder. Medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 4 publications
0
10
0
2
Order By: Relevance
“…In acromegaly, an increase in the frequency of goiter was detected as well as in benign and malign thyroid lesions [31]. In recent epidemiological studies, it has been found that the risk of thyroid cancer increases depending on duration of illness in acromegalic patients who have past history of goiter or thyroid nodule [32,33]. In a study by Gaspari et al [34] in 2002, 258 patients with active acromegaly were evaluated for the presence thyroid disorders, and the thyroid cancer rate was found to be 1.2%.…”
Section: Discussionmentioning
confidence: 99%
“…In acromegaly, an increase in the frequency of goiter was detected as well as in benign and malign thyroid lesions [31]. In recent epidemiological studies, it has been found that the risk of thyroid cancer increases depending on duration of illness in acromegalic patients who have past history of goiter or thyroid nodule [32,33]. In a study by Gaspari et al [34] in 2002, 258 patients with active acromegaly were evaluated for the presence thyroid disorders, and the thyroid cancer rate was found to be 1.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller tumors carry a better prognosis than larger tumors. PTCs measuring less than 1 cm in size are called papillary microcarcinomas, and have been reported in 10% to 30% of autopsy studies . In the past, these tumors were incidentally detected in thyroidectomy specimens, but they are now detected with increasing frequency by high‐resolution ultrasound.…”
Section: Differentiated Thyroid Cancermentioning
confidence: 99%
“…For example, the autoimmune inflammatory disorders, chronic Hashimoto's thyroiditis and Graves' disease, are both associated with an increased incidence of papillary thyroid carcinoma (PTC) (11). On the other hand, tumor cells themselves may support their own growth and invasive phenotype through direct expression of inflammation-related molecules (2).…”
mentioning
confidence: 99%